2010
DOI: 10.1179/030192310x12700328925868
|View full text |Cite
|
Sign up to set email alerts
|

Studies of wetting characteristics of liquid Fe–Cr alloys on oxide substrates by sessile drop technique

Abstract: The purpose of this study was to investigate the wetting characteristics of three different oxide substrates (alumina, magnesia and dolomite) in order to examine the work of adhesion of Fe-Cr alloys on these substrates. The contact angle of a liquid drop (Fe-Cr alloy) on the oxide substrates was investigated at 1823 K under a H 2 atmosphere by the sessile drop technique. The contact angle slightly decreased on the alumina and dolomite substrates with increasing chromium concentration, but did not change as muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The wettability between inclusions and molten iron or steel has been widely investigated. [8][9][10][11][12][13][14][15][16][17][18][19][20] However, the values of interfacial energy and contact angle reported in these studies cannot be compared because the studies were conducted under different experimental conditions (e.g., temperature, atmosphere, and crystal orientation). For example, molten Fe and Al 2 O 3 were investigated by Ogino et al, who reported a contact angle of 128° in H 2 atmosphere at 1 873 K. 11) However, Nakashima et al studied the same materials and reported a contact angle of 120° in Ar atmosphere at the same temperature.…”
Section: Evaluation Of Interfacial Energy Between Molten Fe and Fe-18%cr-9%ni Alloy And Non-metallic Inclusion-type Oxidesmentioning
confidence: 99%
“…The wettability between inclusions and molten iron or steel has been widely investigated. [8][9][10][11][12][13][14][15][16][17][18][19][20] However, the values of interfacial energy and contact angle reported in these studies cannot be compared because the studies were conducted under different experimental conditions (e.g., temperature, atmosphere, and crystal orientation). For example, molten Fe and Al 2 O 3 were investigated by Ogino et al, who reported a contact angle of 128° in H 2 atmosphere at 1 873 K. 11) However, Nakashima et al studied the same materials and reported a contact angle of 120° in Ar atmosphere at the same temperature.…”
Section: Evaluation Of Interfacial Energy Between Molten Fe and Fe-18%cr-9%ni Alloy And Non-metallic Inclusion-type Oxidesmentioning
confidence: 99%
“…Over the past two decades, several researchers have addressed the issue of wetting at the interface of Cr-Ni steel and refractory material under different oxygen partial pressure [33][34][35][36][37][38][39]. To the best of our knowledge, no one has addressed the effect of oxygen contained in the order of hundreds of ppm on the interfacial behavior of low-alloy steels containing chromium and nickel.…”
Section: Introductionmentioning
confidence: 99%